Tax and spend : the welfare state, tax politics, and the limits of American liberalism - Michelmore, Molly (Politics and culture in modern America., 2012)
Analyzing economic policy from the New Deal through the Reagan Revolution, Tax and Spend takes a new look at the so-called tax-and-spend liberals of the past. This important study examines why many Americans have come to hate the government but continue to demand the security it provides.